Pengaruh kecemasan dan self-efficacy siswa terhadap pemahaman konsep matematika SMP kelas VII tahun ajaran 2020/2021 (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2021)
The research was conducted at SMP Negeri 4 Ungaran with the aim of knowing the effect of anxiety and self-efficacy on the understanding of mathematics concepts in grade VII junior high school students in the 2020/2021 academic year. This type of research is correlational research with quantitative methods. The population in this study were all students of class VII, while the subjects were students of class VII A. The instruments used in this study were a test instrument for understanding mathematical concepts and a non-test instrument in the form of an anxiety scale and a self-efficacy scale. The results of the study using simple linear regression conclude that there is a negative relationship between anxiety and concept understanding, and there is a positive relationship between self-efficacy and concept understanding. If the results of the study using multiple linear regression provide the conclusion that anxiety and self-efficacy together affect conceptual understanding.
Keywords: anxiety; self-efficacy; concept understanding